Enhancing Public Sector IT Governance through COBIT 2019: A Case Study on Service Continuity and Data Management in the Central Lombok - Bagja, Amir; Amri, Zaenul; Imtihan, Khairul; Rodi, Muhamad; Rusniatun, Siska Yuni (Journal of Information System and Informatics, 2024)
This study evaluates the IT governance maturity of the Central Lombok Civil Service Police Unit (Satpol PP) using the COBIT 2019 framework, focusing on improving service continuity and data security in a resource-constrained public sector context. The assessment, conducted across key domains such as service delivery, data security, and compliance, revealed that Satpol PP operates at Level 3 (Defined) maturity. While processes are documented and standardized, significant gaps remain in automation, proactive risk management, and real-time monitoring. These limitations hinder the organization's ability to optimize service continuity and safeguard sensitive data effectively. The study emphasizes the innovative application of COBIT 2019 in a resource-limited environment, demonstrating how the framework can be adapted to prioritize immediate needs while progressively advancing IT governance maturity. Key recommendations include automating monitoring systems, enhancing data security protocols, and implementing proactive risk management strategies. These findings contribute valuable insights into the challenges and solutions for IT governance in public institutions, providing a replicable model for similar organizations. Future research should explore the long-term impacts of these recommendations on IT governance maturity and service efficiency in other public sector contexts.